2022
DOI: 10.3389/fpubh.2022.977958
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional energy poverty and depression among China's older adults

Abstract: Older adults often face more pronounced energy inequality in their daily lives, which is one of the reasons for their accumulation of stress or anxiety and may further aggravate their depression. Analyzing the relationship between energy poverty and the depression level of China's older adults will provide policy enlightenment for solving the problems of older adults' relative poverty, energy poverty, and mental poverty and thus promote happy and healthy aging. In this paper, using the data of China Health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In contrast with urban residents, who heavily rely on energy-consuming active cooling equipment, rural dwellers prefer traditional cooling strategies (e.g., using a fan ). Besides the consumption value “frugality,” energy poverty ( 51 ) and low income ( 52 ) make rural dwellers reluctant to pay much for cooling. We hope that mounting studies on rural dwellers' strategy of using air-conditioners for cooling will appear in recent years and that the differences in health effects between using traditional cooling strategies and air-conditioners can be deeply investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with urban residents, who heavily rely on energy-consuming active cooling equipment, rural dwellers prefer traditional cooling strategies (e.g., using a fan ). Besides the consumption value “frugality,” energy poverty ( 51 ) and low income ( 52 ) make rural dwellers reluctant to pay much for cooling. We hope that mounting studies on rural dwellers' strategy of using air-conditioners for cooling will appear in recent years and that the differences in health effects between using traditional cooling strategies and air-conditioners can be deeply investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The Marmot Review, one of the most widely cited reports on the Health Impacts of Cold Homes and Fuel Poverty [22], found a strong relationship between cold temperatures and cardiovascular and respiratory diseases, reconstructing links between cold housing and minor illnesses such as colds and flu. Beyond the physical consequences of inadequate housing on human wellbeing, in the literature, poor mental health has also been associated with conditions of energy poverty, implicating social isolation and anxiety in poor living conditions, debt management, and inadequate temperature conditions [22][23][24][25][26][27][28]. For decades, specific population groups have been described as being most vulnerable to the effects of low temperatures, including the elderly, children, and people with disabilities and existing physical or mental health conditions [29][30][31].…”
Section: State Of the Artmentioning
confidence: 99%
“…Energy inequality has become a significant research topic due to its social, economic, and environmental implications. Researchers from a wide range of disciplines, including social sciences, economics, public policy, and even engineering, are now exploring different aspects of energy inequality, such as the factors that contribute to energy inequality, the economic and social impacts of energy inequality [8][9][10][11][12][13][14][15], the impact on health [13,[16][17][18][19][20][21][22][23], the impact on vulnerable members of the society [24][25][26][27][28][29], the impact on environmental quality [30][31][32][33][34][35][36], and the policies and strategies that can help to promote energy access and equity. Recent advancements in data collection and analysis have also enabled researchers to better understand the magnitude and distribution of energy inequality across different regions and populations.…”
Section: The Conceptmentioning
confidence: 99%
“…This systematic literature review has identified that various terms are used to address similar aspects of energy inequality (see Figure 1) [17], including energy poverty [9,14,18,20,21,26,32,37], energy insecurity [17,38], fuel poverty [39][40][41][42][43], environmental inequality [34], carbon inequality [44], and environmental degradation [13,31,36]. To achieve the objective of this study, which is to identify energy inequality dimensions and their indicators and explore ways to reduce them, it is crucial to establish a common understanding and terminology.…”
Section: The Conceptmentioning
confidence: 99%
See 1 more Smart Citation